ANÁLISE VISUAL DA ESTRUTURA DO SOLO EM ÁREAS DE CULTIVO DE CANA-DE-AÇÚCAR - SILVA, Fagner Luiz Rodrigues; GUIMARÃES JUNNYOR, Wellingthon da Silva; DE MARIA, Isabella Clerici; FLORA, Murillo Pereira; PAES, Leilane Lilia; RODRIGUES, Gustavo Sanches (ANAIS DO ENIC, 2022)
-